Scribal culture and the making of the Hebrew Bible - Toorn, K. van der (Harvard University Press, 2009)
The scribes of ancient Israel are indeed the main figures behind the Hebrew Bible, and this book tells their story for the first time. Drawing comparisons with the scribal practices of ancient Egypt and Mesopotamia, van der Toorn details the methods, assumptions, and material means that gave rise to biblical texts. Traditionally seen as the copycats of antiquity, the scribes emerge here as the literate elite who held the key to the production and the transmission of texts.